(untitled) (Bulletin KNOB, 1992)
The architecture of the fortress engineer Allessandro Pasqualini - an Italian working in the Netherlands during the second quarter of the sixteenth century - is characteristic of the ’austere’ Renaissance. This notion is reserved for a group of buildings in the Netherlands of this period, designed by Italians. Pasqualini applied the classical orders as consistently as possible in various building types. In this respect he differed radically from his mannerist Dutch contemporaries, who used classical elements in a very free and inventive fashion. Pasqualini’s sources for his classical architecture were, however, very limited. He drew extensively on the illustrations in Cesariano’s edition of Vitruvius, but these examples did not provide him with all the answers to the problems he had to deal with. In the church tower of IJsselstein and the chapel of the Gulik castle he showed himself rather successful at adapting the examples of Cesariano. The gable of the church of St. Elizabeth in Grave confronted him with problems he could evidently not cope with. Besides, he appears to have been ignorant of older and contemporary Italian Renaissance architecture. Nevertheless, even in this gable we can discern his attempts at a strict application of the classical rules as derived by him from Cesariano.